A COVID charter, a better world - Miller, Toby 1958- (Rutgers University Press, 2021)
With unprecedented speed, scientists have raced to develop vaccines to bring the COVID-19 pandemic under control and restore a sense of normalcy to our lives. Despite the havoc and disruption the pandemic has caused, it's exposed exactly why we should not return to life as we once knew it. Our current profit-driven healthcare systems have exacerbated global inequality and endangered public health, and we must take this opportunity to construct a new social order that understands public health as a basic human right. A COVID Charter, A Better World outlines the steps needed to reform public policies and fix the structural vulnerabilities that the current pandemic has made so painfully clear. Leading scholar Toby Miller argues that we must resist neoliberalism's tendency to view health in terms of individual choices and market-driven solutions, because that fails to preserve human rights. He addresses the imbalance of geopolitical power to explain how we arrived at this point and shows that the pandemic is more than just a virus-it's a social disease. By examining how the U.S., Britain, Mexico, and Colombia have responded to the COVID-19 crisis, Miller investigates corporate, scientific, and governmental decision-making and the effects those decisions have had on disadvantaged local communities. Drawing from human rights charters ratified by various international organizations, he then proposes a COVID charter, calling for a new world that places human lives above corporate profits